Systematic comparison between photonic sensors based on dielectrics and metals - Soares, Rodrigo Romão França (2020)
Photonic biosensors have gained much attention recently due to their high sensitivity, low energy consumption and miniaturization capability; in the near future, these sensors will form the basis of the so-called Lab on a Chip: a device capable of performing accurate clinical analyzes in a single chip and in any location, being of great help in countries with few resources for disease detection. There are several configurations for biophotonic sensors ranging from fiber-optic based systems, waveguides, resonators, to nanoparticles and photonic crystals, to name a few. In spite of this great diversity, constituted by dielectric or metallic media, these devices can be classified in two broad categories: those that require previous mode coupling and those that do not. The purpose of this dissertation is to study the devices of the second category, focusing on the so-called quasi-guided modes, presenting the physical phenomena involved and the main tools used to evaluate their performances. Therefore, using numerical simulations, present a comparative study between dielectric and metallic systems. Finally, a dielectric based biosensor is proposed, aiming on obtaining the similar performances of devices based on metal.